Correlation of academic emotion and hardiness personality of undergraduate nursing students - Lili Guo; Danfeng Yan; Junping Yan; Rui Jiao (BMC Nursing, 2024)
Abstract Background Academic emotion is a fundamental emotional concept closely linked to academic achievement. Understanding the connection between academic emotion and the personality trait of hardiness is pivotal in maintaining a stable career orientation throughout one's educational career. Therefore, in pursuit of fostering the robust growth of nursing careers, it is imperative to delve into the academic emotions experienced by undergraduate nursing students. This study endeavors to mitigate the impact of gender differences among nursing students while investigating the intricate relationship between academic emotions and the trait of hardiness in their personalities. Methods This study employed a cross-sectional research design. We gathered data from a convenient sample of 292 nursing students enrolled at Shanxi University of Chinese Medicine. Each student provided demographic information and responded to a general academic mood questionnaire, as well as a Hardiness Personality Rating Scale. Subsequently, we used canonical correlation analysis to evaluate the correlation between academic emotion and tenacity personality in 292 undergraduate nursing students. Results We discovered that academic emotions among nursing students are predominantly characterized by feelings of disappointment and boredom. Furthermore, personality hardiness is primarily influenced by the dimensions of engagement and control. It is important to note that a heightened level of negative, low-arousal academic emotions can diminish the level of engagement. The first typical correlation coefficient corresponding to academic emotion and hardiness were 0.660. The linear combination of standardized variables of the first typical variable corresponding to academic emotion (X1) = -0.444*negative hyperarousal -0.443 * positive hyperarousal + 0.694 * negative hypoarousal -0.260 * positive hypoarousal. The standardized variable equation of the first typical variable corresponding to hardiness personality (η1) = 0.235* hardiness -0.433* control -0.530* investment -0.303* challenge. Conclusions Nursing students generally believe that their input is out of proportion to the return, and this unbalanced emotional experience will seriously affect their academic emotions in China. It is suggested that paying attention to cultivating their tenacious personality traits in the teaching process may help to enhance their academic emotions and enhance the sense of belonging and identity of nursing students engaged in the nursing profession.